2019
DOI: 10.1093/ibd/izz016
|View full text |Cite|
|
Sign up to set email alerts
|

The Unsolved Link of Genetic Markers and Crohn’s Disease Progression: A North American Cohort Experience

Abstract: Background While progress has been made in the identification of Crohn’s disease (CD) susceptibility loci, efforts to identify a genetic basis for disease progression have been less fruitful. The specific aim of this study was to build upon the major genetic advances made in IBD by applying genome-wide technologies toward predicting disease progression in CD. Methods Crohn’s disease cases (n = 1495) from 3 IBD centers were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 69 publications
0
25
0
1
Order By: Relevance
“…ATPBD4 (or DPH6) is a proteincoding gene that regulates adenosine triphosphate (ATP) binding and diphthamide synthase activity, within the protein metabolism pathway (Chertow 1981;Young et al 2004). Polymorphisms in this gene were associated-in various genome-wide association studies (GWAS)-with adiposity (Kichaev et al 2019;Pulit et al 2019), cognitive function (Lee et al 2018;Li et al 2015), and Crohn's disease progression (O'Donnell et al 2019). FARS2 is a protein-coding gene that regulates the translation of mitochondrial proteins and gene expression (Bullard et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…ATPBD4 (or DPH6) is a proteincoding gene that regulates adenosine triphosphate (ATP) binding and diphthamide synthase activity, within the protein metabolism pathway (Chertow 1981;Young et al 2004). Polymorphisms in this gene were associated-in various genome-wide association studies (GWAS)-with adiposity (Kichaev et al 2019;Pulit et al 2019), cognitive function (Lee et al 2018;Li et al 2015), and Crohn's disease progression (O'Donnell et al 2019). FARS2 is a protein-coding gene that regulates the translation of mitochondrial proteins and gene expression (Bullard et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies showed that IBD is spreading widely throughout the world leading to a public health challenge worldwide ( Zheng H. et al, 2017 ; Windsor and Kaplan, 2019 ; Kaplan and Windsor, 2021 ). It is widely accepted that the IBD pathogenesis results from an interplay between gut microbiota and the host immune system with the predisposition of genetic susceptibility and environmental factors ( Ma et al, 2019 ; O’Donnell et al, 2019 ; Ramos and Papadakis, 2019 ; Pang et al, 2021 ). The microbiome-immune system interaction leads to improper immune activation responsible for the clinical and endoscopic observations in IBD patients ( Ramos and Papadakis, 2019 ; Zheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, it is not clear whether polymorphisms that affect IBD risk also contribute to disease course and severity. While O’Donnell et al [ 37 ] report association of 8 SNPs with time to-abdominal surgery, Lee et al [ 38 ] could not identify any associations of disease susceptibility loci with disease prognosis, but identified four loci with significant association to the course of CD without any association to disease susceptibility. In addition, TLR SNPs that do not affect disease susceptibility, were found to be associated with extensive colonic disease in both CD and UC patients [ 39 ], and polymorphisms associated with smoking behavior could predict the number of surgeries and the time to first intestinal surgery in smoking Crohn’s disease patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%